IMPLEMENTASI 7 KEBIASAAN ANAK INDONESIA HEBAT PADA TINGKAT DISIPLIN SISWA SD KELAS 3 - Nadzifa Abidah, Ainnun; Zuni Eka Tiyas Rifayanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Elementary school student discipline, particularly in the lower grades, remains a real challenge in educational practice in Indonesia. In third grade, discipline plays a crucial role because students are in a transitional period of developing responsibility and learning habits. This study aims to describe the implementation of the 7 Habits of Great Indonesian Children and its impact on the discipline level of third-grade students at Al-Hikmah Islamic Elementary School. The study used a qualitative, descriptive approach. Data were collected through observation, interviews with class teachers, students, and the principal, and documentation. Data validity was maintained through triangulation of sources and techniques.The research results show that the implementation of the 7 Habits of Great Indonesian Children has been running well and integrated into daily school activities. Most indicators of student discipline, including time discipline, attitude, responsibility, and compliance with rules, were consistently observed. Routine habits, teacher role models, and support from school policies contributed positively to improving student discipline. However, obstacles remained in the area of ​​time discipline, influenced by students' habits within the family environment.This study concludes that the 7 Habits of Great Indonesian Children is an effective strategy for strengthening character education and fostering discipline in third-grade elementary school students. Successful implementation requires ongoing collaboration between schools and parents to ensure optimal discipline development.